Pediatric Severe Sepsis and Shock in Three Asian Countries: A Retrospective Study of Outcomes in Nine PICUs. Issue 8 (1st March 2021) - Samransamruajkit, Rujipat; Wong, Judith Ju-Ming; Smathakane, Chutima; Anantasit, Nattachai; Sunkonkit, Kanokkarn; Ong, Jacqueline; Lee, Olive Pei Ee; Lee, Pei-Chuen; Phumeetham, Suwannee; Sultana, Rehena; Lapwanich, Usa; Lee, Jan Hau; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Pediatric sepsis remains a major health problem and is a leading cause of death and long-term disability worldwide. This study aims to characterize epidemiologic, therapeutic, and outcome features of pediatric severe sepsis and septic shock in three Asian countries. DESIGN: A multicenter retrospective study with longitudinal clinical data over 1, 6, 24, 48, and 72 hours of PICU admission. The primary outcome was PICU mortality. Multivariable logistic regression analysis was used to identify factors at PICU admission that were associated with mortality SETTING: Nine multidisciplinary PICUs in three Asian countries. PATIENTS: Children with severe sepsis or septic shock admitted to the PICU from January to December 2017. INTERVENTION: None. MEASUREMENT AND MAIN RESULTS: A total of 271 children were included in this study. Median (interquartile range) age was 4.2 years (1.3–10.8 yr). Pneumonia (77/271 [28.4%]) was the most common source of infection. Majority of patients (243/271 [90%]) were resuscitated within the first hour, with fluid bolus (199/271 [73.4%]) or vasopressors (162/271 [59.8%]). Fluid resuscitation commonly took the form of normal saline (147/199 [74.2%]) (20 mL/kg [10–20 mL/kg] over 20 min [15–30 min]). The most common inotrope used was norepinephrine 81 of 162 (50.0%). Overall PICU mortality was 52 of 271 (19.2%). Improved hemodynamic variables (e.g., heart rate, blood pressure, and arterial lactate) were seen in survivors within 6 hours of admission as compared to nonsurvivors. In the multivariable model, admission severity score was associated with PICU mortality. CONCLUSIONS: Mortality from pediatric severe sepsis and septic shock remains high in Asia. Consistent with current guidelines, most of the children admitted to these PICUs received fluid therapy and inotropic support as recommended.